Description of Implementation of Self-Regulated Learning on Student at The University of X - Yan Andre Peranginagin; Budi Sulaeman; Antonina Pantja Juni Wulandari (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
This research aims to provide a description regarding the implementation of Self-Regulated Learning on students at the University of X. This research was organized with quantitative methods with types of descriptive. Sampling method on this research using the technique of convenience with the number of participants of 110 students of University consist of 48 males and 62 females. Measurement of Self-Regulated Learning conducted using questionnaires which done by researchers based on 3 phases of Self-Regulated Learning, which are: (1) Forethought, (2) Performance and (3) Self-reflection. The result of this research showed that applying on the first phases which is the stage of Forethought relatively low with the gain of score of 2.62 compared to an average score of 2.82. However, the second phases, which is the stage of performance relatively high with the gain of score above average which is 2.90. the implementation of the third phases which the self-reflection quite high with the score of 2.94. On the research also found the relationship between Grade Point Average (GPA) and the implementation of the 3 phases of Self-Regulated Learning, which is the higher GPA score earned by students, the more optimal the implementation of 3 cycles of Self-Regulated Learning.